Pharmacokinetics of β-Alanine Using Different Dosing Strategies - Stautemas, Jan; Everaert, Inge; Lefevere, Filip B. D.; Derave, Wim (Frontiers in Nutrition, 2018)
Introduction. The ergogenic response following long-term ingestion of β-alanine shows a high inter-individual variation. It is hypothesized that this variation is partially caused by a variable pharmacokinetic response induced by inferior dosing strategies. At this point most supplements are either taken in a fixed amount (x g), as is the case with β-alanine, or relative to body weight (x g per kg BW), but there is currently neither consensus nor a scientific rationale on why these or other dosing strategies should be used. The aim of this study is to objectify and understand the variation in plasma pharmacokinetics of a single oral β-alanine dose supplemented as either a fixed or a weight-relative dose (WRD) in an anthropometric diverse sample. Methods. An anthropometric diverse sample ingested a fixed dose (1400 mg) (n = 28) and a WRD of BA (10 mg/kg BW) (n = 34) on separate occasions. Blood samples were taken before and at nine time points (up to 4 hours) after β-alanine ingestion in order to establish a pharmacokinetic profile. Incremental area under the curve (iAUC) was calculated by the trapezoidal rule. Plasma β-alanine was quantified using HPLC-fluorescence. Results. The variation coefficient (CV%) of the iAUC was 35.0% following ingestion of 1400mg β-alanine. Body weight explained 30.1% of the variance and was negatively correlated to iAUC (r = -0.549; p = 0.003). Interestingly, the CV% did not decrease with WRD (33.2%) and body weight was positively correlated to iAUC in response to the WRD (r = 0.488; p = 0.003). Conclusion. Both dosing strategies evoked an equally high inter-individual variability in pharmacokinetic plasma profile. Strikingly, while body weight explained a relevant part of the variation observed following a fixed dose, correction for body weight did not improve the homogeneity in β-alanine plasma response. We suggest to put more effort into the optimization of easy applicable and scientifically justified personalized dosing strategies.